A test of social learning and parent socialization perspectives on the development of perfectionism. (1st July 2020) - Curran, Thomas; Hill, Andrew P.; Madigan, Daniel J.; Stornæs, Annett V.
Highlights: Parent perfectionism positively predicted child perfectionism. These relationships were accounted for, in part, by conditional regard. Parent perfectionism directly and indirectly contributes to child perfectionism. Abstract: Theory and research indicate that perfectionism can be intergenerationally transmitted by, among other things, social learning (e.g., parental imitation) and controlling forms of parental socialization. The current study extends this literature by combining and testing these ideas in a mediation model whereby child reported self-oriented and socially prescribed is the result of both parent reported self-oriented and socially prescribed perfectionism and child perceptions of parental conditional regard. One hundred and fifteen parent-child dyads (parent M age = 46.93 years, SD  = 5.41; child M age = 14.11 years, SD  = 1.87) completed a standardised questionnaire. Path analysis revealed that child self-oriented and socially prescribed perfectionism were positively predicted by parent self-oriented and socially prescribed perfectionism and that these relationships were accounted for, in part, by child perceptions of parental conditional regard. Our findings indicate that combining social learning and parent socialization perspectives provide a fuller understanding of the intergenerational transmission of perfectionism.